114 Should we Standardise how Heart Rate is Measured?. (31st May 2014) - Mohee, Kevin; Khan, Muhammad Murad; Akeroyd, Miss Louise; Scally, Andrew John; Morley, Chris
Abstract : Introduction: There is increasing evidence that lowering HR in cardiovascular disease may be beneficial. Recent trials have documented heart rate (HR) using supine ECG and the NICE guideline for heart failure[1, 2] suggests lowering HR below 75 bpm but without specifying how HR should be measured. There is no published data on how HR measured by supine ECG compares to "real world" measurement in the clinic or surgery and any discrepancy might lead to overzealous introduction of HR lowering treatment. Method: HR was measured in 136 consecutive patients attending a new cardiology OP clinic. Three methods of measuring HR were compared in the following sequence: Supine HR measured by ECG "real world" measurement by the nurse using Dynamat (auto) Manually over 30 sec during examination (Dr). Patients with dysrhythmia were excluded. Findings: HR measured using these 3 methods has been presented separately and has shown a significant difference with ECG HR slower on average by >6bpm vs. either auto or Dr Measurement. The table shows the number and % of patients where HR was either ≥ 70bpm (Shift evidence) or ≥ 75 bpm (Nice guidelines) measured by one or two methods but not all three. Conclusion: Real world HR measurement is consistently higher than supine ECG HR and may therefore lead to over inclusive treatment according to guideline recommendations. The method used to measure HR should be defined both in clinical trials and in published guidelines. Supine ECG is suggested as the preferred method for documenting HR prior to initiating rate lowering therapy. References: Hardman SM. Ivabradine in heart failure: NICE guidance. Heart, 2013 Simel DL. NICE guideline for management of chronic heart failure in adults. Ann Intern Med . 2012;156(1 Pt 1): p. 69-70; author reply 70